Penerapan Metode Kooperatif Model Group Investigation dalam Meningkatkan Prestasi Belajar Pendidikan Jasmani Olahraga dan Kesehatan Siswa Kelas IV SD - Al Imran (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
The purpose of this study was to find out how far the understanding and mastery of the PJOK thematic subjects about Floor Gymnastics and Rhythmic Gymnastics after the implementation of the GI cooperative learning model in Grade IV students of UPT SDI No. 33 Sumpang Binangae. The research method used is this research is action research (action research), because research is conducted to solve learning problems in the classroom. Based on the results of the research and discussion, it can be concluded that cooperative learning of the GI model has a positive impact on improving student learning achievement which is marked by an increase in student learning completeness in each cycle, namely cycle I (66.67%) with a percentage of completeness of 22.22% learning completeness cycle II (79.72%) with a completeness percentage of 87.73%, and cycle III (88.61%) with a completeness percentage of 91.25%.